The role of Applied Higher Education in achieving the SDGs: The Example from the Faculty of Vocational Studies at Universitas Airlangga - Damar Kristanto; Mochammad Soleh; Novianto Edi Suharno; Gagas Gayuh Aji (Universitas Airlangga, 2021)
Abstractthe whole world has been made aware of the importance of sustaining human life on this earth. The economic improvement felt in the last decade is the result of increasing industrialization around the world. This has a fairly serious impact in terms of natural damage and social life. Fundamental changes are urgently needed to break the chain of socio-environmental damage that threatens the survival of future generations. These fundamental changes can be started from changes in the concept of education. Education is still considered the key to development both in terms of human resources and innovation. Applied education can be a door in the teaching of new abilities and skills based on the SDGs. This study aims to describe the role of applied or vocational education in achieving SGDs. The Faculty of Vocational Studies at Universitas Airlangga can be an example of how applied higher education institutions have the potential to achieve the SDGs goals. Based on the results of our study, it appears that the role of applied educational institutions has the potential to achieve the SDGs targets. The results of this study have a significant impact on future policy directions and institutional development. Keywords: SDGs, higher education institution, sustainable development, thematic analysis.